Domestic violence against women: Perception and conceptions based on the oral history of victims (Revista Contexto & Saúde, 2023)
Objective: To reveal the expressions and conceptions of domestic violence unleashed on women who have broken the cycle of violence. Method: Qualitative research based on the Oral History method, conducted through interviews with seven women from the two largest municipalities in a metropolitan region in the interior of Ceará, Brazil, and systematized through Thematic Analysis. Results: Seven women aged between 34 and 65 years, heterosexual, mostly single or divorced, black and brown, with an average income of one minimum wages, took part in the research. Domestic violence was manifested through physical, psychological and sexual aggression. The expressions of violence evidenced result in physical and psychological consequences, the latter being more impactful and accompanying women throughout their lives. The way out of an abusive relationship is complex and hampered by fear, shame and social isolation resulting from an abuse routine. Final Considerations: The study emerges to a conception of complex violence, in addition to physical aggressions and showing expressions of psychological and sexual violence, revealing how women perceive the violence suffered.